Ag and N co-doped TiO2 nanostructured photocatalyst for printing and dyeing wastewater. (April 2017) - Chen, Qingliang; Zhang, Yulian; Zhang, Dongdong; Yang, Yingqin
Graphical abstract: Abstract: Ag and N co-doped TiO2 nanoparticles were synthesized by the sol–gel method. Tetrabutyl titanate was used as the precursor, AgNO3 as the Ag source, and urea as the N source. When the sol was prepared, a 304 stainless steel mesh as the structured material was immerged into the solution. After calcinated at preset temperature, nanostructured photocatalysts were obtained. The photocatalysts were located at the internal shell of a continuous reactor that was designed for photocatalytic reaction. The degradation reaction of methylene blue was carried out in this reactor. The characteristics and doping dosage of the nanostructured photocatalysts were analyzed by thermogravimetric analysis, X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, transmission electron microscopy, and energy dispersive X-ray spectroscopy. The degradation product samples were determined by UV–vis spectrometry. Finally, the photocatalytic efficiency was evaluated under batch and continuous reactors. The multifarious kinetic constants were determined under reaction conditions. The result illustrates that the degradation efficiency of methylene blue apparently increased.